Sensitive training through body awareness to improve the writing of patients with writer's cramp - Flavia Quadros Boisson Waissman; Marco Orsini; Osvaldo J.M. Nascimento; Marco Antônio A. Leite; João Santos Pereira (MDPI AG, 2013)
The aim of this article is to evaluate if body awareness is important to improve the writing ability before using the splints. Twelve patients with writer's cramp were evaluated by a specialist in movement disorders. The Burke-Fahn-Marsden Scale (BFM), the Jedynak Protocol and the Analog Pain Scale were used. The rehabilitation training was administered over an eight-week period, in two phases of four weeks each, twice a week. Each session would last 60 minutes. A significant improvement was shown, not only in the motor, but also in the pain perception, through the BFM scale, the Jedynak Protocol and the Analog Pain Scale. Therefore, we conclude that the motor training, thanks to the body awareness and immobilization by splints of the affected dystonic musculature, led to an important improvement in the writer's cramp writing.